Circulating Cytokines and Growth Factors in Pediatric Pulmonary Hypertension - Mark Duncan; Brandie D. Wagner; Keri Murray; Jenna Allen; Kelley Colvin; Frank J. Accurso; D. Dunbar Ivy (Mediators of Inflammation)
Background. Management of pediatric pulmonary hypertension (PH) remains challenging. We have assessed a panel of circulating proteins in children with PH to investigate their value as predictive and/or prognostic biomarkers. From these determinations, we aim to develop a practical, noninvasive tool to aid in the management of pediatric PH. Methods. Twelve cytokines and growth factors putatively associated with lung or vascular disease were examined in plasma specimens from 70 children with PH using multiplex protein array technology. Associations between hemodynamics, adverse events, and protein markers were evaluated. Results. Epidermal growth factor (EGF) and IL-6 were associated with important hemodynamics. Of the twelve proteins, VEGF and IL-6 were significantly, univariately associated with the occurrence of an adverse event, with odds ratios (95% confidence intervals) of 0.56 (0.33–0.98) and 1.69 (1.03–2.77), respectively. When hemodynamic predictors were combined with protein markers, the ability to predict adverse outcomes within the following year significantly increased. Conclusions. Specific circulating proteins are associated with hemodynamic variables in pediatric PH. If confirmed in additional cohorts, measurement of these proteins could aid patient care and design of clinical trials by identifying patients at risk for adverse events. These findings also further support a role for inflammation in pediatric PH.